PEMANFAATAN INSTRUMEN KOMPAS KIBLAT RHI DALAM PENGUKURAN ARAH KIBLAT MASJID AS SALAM MEDAN SUNGGAL - M. Arbisora Angkat (An Natiq, 2022)
BHR (Badan Hisab Rukyat) North Sumatra Province revealed that it is oftentimes for qibla direction of mosques in Medan City which does not face the Ka’bah or Masjidil Haram, but to the west and South Africa. This attracted the author's attention to examine the qibla direction of mosques in Medan City, especially As Salam Mosque Medan Sunggal. This research aims to find out how to measure the Qibla direction using Kompas Kiblat RHI instrument so that it is known as the qibla azimuth of As Salam Mosque Medan Sunggal. This research uses a qualitative analysis technique by describing the results of measuring qibla direction of As Salam Mosque in Medan Sunggal using Kompas Kiblat RHI instrument. After measuring, it is known that the Qibla azimuth of As Salam Mosque Medan Sunggal is 292o 47' 09.83" UTSB (North–East–South–West).